Penggunaan Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Komunikasi Matematis Dan Pengaruhnya Terhadap Self Regulated Learningsiswa Sekolah Menengah Pertama - Mulyani, Has (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2020)
The importance of mathematical and communication skills Self Regulated Learning for students has been widely recognized in mathematics education. But still lack a way that can be used in improving keduanya, into the implementation of the basic idea of this research. Through the application of problem-based learning is expected to enrich the strategy to improve the communication skills of mathematical and Self Regulated Learning students. This research includes studies quasi experimental design with a control group not equivalent. This research was conducted in SMP Pasundan 2 Bandung, the subject of the entire population of students of class VII SMP Pasundan 2 Bandung and took two samples of class VII. Instruments used include test questions and questionnaires mathematical communication skills Self Regulated Learning. Quantitative data analysis using ANOVA test two way, followed by Scheffe test. Based on the results of this study concluded that: increase of mathematical and communication skills Self Regulated Learning Ability Early learners with Mathematics (LAM) high, medium and low learning using Problem Based Learning is better than the increase in mathematical and communication skills Self-Regulated Learning learners who use the usual learning model. Then this study suggests that there is a correlation between communication skills matematis and Self Regulated Learning. The correlation coefficient between the two is 0.643 with the criteria of being